Microneedle-Assisted Transfersomes as a Transdermal Delivery System for Aspirin - Raha Rahbari; Lewis Francis; Owen J. Guy; Sanjiv Sharma; Christopher Von Ruhland; Zhidao Xia (Pharmaceutics, 2023)
Transdermal drug delivery systems offer several advantages over conventional oral or hypodermic administration due to the avoidance of first-pass drug metabolism and gastrointestinal degradation as well as patients’ convenience due to a minimally invasive and painless approach. A novel transdermal drug delivery system, comprising a combination of transfersomes with either solid silicon or solid polycarbonate microneedles has been developed for the transdermal delivery of aspirin. Aspirin was encapsulated inside transfersomes using a “thin-film hydration sonication” technique, yielding an encapsulation efficiency of approximately 67.5%. The fabricated transfersomes have been optimised and fully characterised in terms of average size distribution and uniformity, surface charge and stability (shelf-life). Transdermal delivery, enhanced by microneedle penetration, allows the superior permeation of transfersomes into perforated porcine skin and has been extensively characterised using optical coherence tomography (OCT) and transmission electron microscopy (TEM). In vitro permeation studies revealed that transfersomes enhanced the permeability of aspirin by more than four times in comparison to the delivery of unencapsulated “free” aspirin. The microneedle-assisted delivery of transfersomes encapsulating aspirin yielded 13-fold and 10-fold increases in permeation using silicon and polycarbonate microneedles, respectively, in comparison with delivery using only transfersomes. The cytotoxicity of different dose regimens of transfersomes encapsulating aspirin showed that encapsulated aspirin became cytotoxic at concentrations of ≥100 μg/mL. The results presented demonstrate that the transfersomes could resolve the solubility issues of low-water-soluble drugs and enable their slow and controlled release. Microneedles enhance the delivery of transfersomes into deeper skin layers, providing a very effective system for the systemic delivery of drugs. This combined drug delivery system can potentially be utilised for numerous drug treatments.